HUBUNGAN ANTARA GAYA HIDUP, OBESITAS, RIWAYAT KELUARGA DENGAN KEJADIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS TOMIA KECAMATAN TOMIA KABUPATEN WAKATOBI - Harni; Rininta Andriani; Dahmar Dahmar; Muhamad Subhan (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2023)
One of the non-communicable disease that are currently a priority in the world of global health is hypertension. Hypertension is an increase in sytolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Based on data obtained from the Tomia health center, hypertension data in the last 3 years in 2020 was 240, in 2021 as many as 2022 it decreased by 111. The purpose of this study was to determine the relationship between lifestyle, obesity, familiy history and the incidence of hypertension in the region. Tomia Public Health Center, Tomia Distric, Wakatobi Regency.The research method is quantitative with a cross sectional study approach. The number of sample in this study was conducted by simple random sampling method. The source of data in this study is primary data and secondary data. The data analysis used in this research is univruate analysis and bivariate analysis. Using α 0,05 square test. Data were analyzed using SPSS 21.The research results show that there is no relationship between physical activity lifestyle (p-value = 0.206> 0.05), diet (p-value = 0.119> 0.05), there is a relationship betwee smoking habits (p-value = 0.005< 0.05), there is no relationship between obesity (p-value = 0.066> 0.05), and there is no relationship betwwen familiy history (p-value = 0.075> 0.05 ) with the incidence of hypertension in the working area of the Tomia health center.The conclusion of this study is that there is a relationship between smoking habits and no relationship between physical activity, eating patterns, obesity and family history with the incidence of hypertension in the working area of the Tomia Public Health Center. Suggestions in this study are that people should do early blood pressure checks because hypertension increases with age.